Pests in plantation forests: Challenging traditional productive paradigms in the Southern Cone of America - Villacide, Jose Maria; Fuentealba, Alvaro (Elsevier, 2025)
Commercial forest plantations in the Southern Cone of South America, dominated by Pinus and Eucalyptus, are increasingly affected by pests, primarily driven by global change and silvicultural intensification. The predominance of homogeneous stands composed of fast-growing exotic tree species under high-input regimes reduces biodiversity and increases vulnerability to both invasive and native pests. This review aims to assess the potential of mixed-species plantations to enhance pest resilience in plantation forests of the region. Recent changes in pest-host dynamics, including novel associations and spillovers into native forests, underscore the growing complexity of forest health challenges in the region. In this context, forest diversification, through mixed-species plantations and increased landscape heterogeneity, has emerged as a promising approach to enhance ecological resilience and reduce pest impacts. Although empirical evidence from the region remains limited, studies suggest that greater tree diversity can reduce pest incidence by hindering host detection and promoting more effective natural enemy communities. The effectiveness of such diversification, however, depends on species composition, ecological interactions, and management context. Regionally coordinated experimental networks are urgently needed to guide the transition toward more resilient silvicultural models. These should evaluate pest-specific responses, productivity trade-offs, and long-term forest health outcomes under diverse management scenarios. Effective implementation will also require strong policy support, including incentives for diversification, harmonized technical protocols, and sustained investment in research infrastructure. By integrating ecological principles into plantation forest system design and promote regional collaboration, the Southern Cone of America can lead the development of sustainable, pest-resilient plantation forestry under global change.